Human Disciplines: Similarities Between Science and Theology - Prevot, Andrew L. (Philosophy, theology and the sciences, 2023)
The Science-Engaged Theology (SET) Foundations 2022 summer seminar brought together theologians and philosophers of science to discuss theories of inference, data, measurement, modeling, and more. Reflecting on his experience as a theologian in residence at this seminar, the author argues that recent developments in the philosophy of science that emphasize the interpretive, practical, and pluralistic features of scientific practice reveal a methodological closeness with contemporary theology. Revisiting the scholastic question of whether theology is a science, the author answers in the negative. Nevertheless, the author contends that there are striking similarities between theology and science in their current modes of operation.